2023
DOI: 10.1039/d3fo01902k
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic acid, a small-molecule natural product, inhibits ECM degeneration in osteoarthritis by regulating the Hippo/YAP and Wnt/β-catenin pathways

Tianwen Ma,
Hongri Ruan,
Liangyu Lv
et al.

Abstract: Over the past few decades, osteoarthritis (OA) has been a major health problem worldwide. It is imminent to develop new, effective, and safe drugs to treat OA. There are many...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Induction of ferroptosis may increase MMPs protein expression and decrease collagen II expression in chondrocytes. 28,29 Overall, the above findings illustrate that silencing IGF2BP1 represses IL-1β-stimulated ferroptosis in primary chondrocytes by enhancing MMP3 mRNA stability. However, the shortcomings of the study are also need our attention and further study to solve the problem.…”
mentioning
confidence: 71%
“…Induction of ferroptosis may increase MMPs protein expression and decrease collagen II expression in chondrocytes. 28,29 Overall, the above findings illustrate that silencing IGF2BP1 represses IL-1β-stimulated ferroptosis in primary chondrocytes by enhancing MMP3 mRNA stability. However, the shortcomings of the study are also need our attention and further study to solve the problem.…”
mentioning
confidence: 71%
“…In addition, with the process of abnormally differentiation and dedifferentiation, the significant enriched pathway for RegC-B was transformed into the Hippo signaling pathway. Most scholars believe that the Hippo-YAP signaling pathway plays a protective role against ( 29 , 30 ), but lack of reports on the role of the Hippo-TAZ pathway in the process of OA cartilage ( 31 ). The results of the current study suggest that Hippo-TAZ should be an important pathway to cause or against OA.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ma et al 112 reported that OA plays a protective role in joints mainly through promoting the secretion of collagen II and inhibiting the secretion of inflammatory cytokines such as IL-1β, TNF-α, MMP-3 and MMP-13. Mechanistically, this therapeutic effect depended on activating the Hippo/YAP pathway, which ultimately resulted in disruption of cartilage degradation.…”
Section: Atdc Cellsmentioning
confidence: 99%
“…Mechanistically, this therapeutic effect depended on activating the Hippo/YAP pathway, which ultimately resulted in disruption of cartilage degradation. 112 Resolvin D1 can modulate the YAP signaling pathway by promoting YAP phosphorylation in synovial cells, inhibiting the secretion of inflammatory factors and promoting the proliferation of aggressive synovial cells to delay the progression of cartilage degradation. 90 Aspirin also has therapeutic effects by mitigating the progression of cartilage degeneration by stabilizing YAP expression to reduce oxidative stress and inflammatory factor levels in vitro.…”
Section: Atdc Cellsmentioning
confidence: 99%